The "Ariadne auf Naxos" of Hugo von Hofmannsthal and Richard Strauss - Daviau, Donald G. (UNC Studies in the Germanic Languages and Literatures, 1975)
This book presents in comprehensive fashion the extraordinary development of "Ariadne auf Naxos" from its conception to the final operatic version. The unique collaboration of Hofmannsthal and Strauss is examined and the classical myths that served as a basis for the libretto are investigated. The detailed analysis and interpretation of both the text and the music demonstrate that this work is epochal in the history of early nineteenth-century opera and commands central importance in the overall production of its authors.